Sistema que vinculé a paciente y profesional, para el correcto desarrollo de ejercicios en la recuperación postquirúrgica para la corrección del Hallux Valgus. - Romero Restrepo, Maureen Alejandra (Universidad Antonio Nariño, 2022)
Hallux Valgus, commonly called "bunion", is a very frequent pathology and one of the triggering factors of most foot ailments, it extends to the entire population, it does not exclude gender, age, demographic factors, races, economic factors , social, political, etc. (Frey¿ C, 1995). Over the years, different types of treatments have been used for this pathology, these range from conventional treatment such as braces, injections, pharmacological, etc. However, they have not shown good results, which is why patients and specialists in this area resort to surgical treatment, fulfilling certain requirements, and then advise starting with a Physiotherapy treatment.